2016
DOI: 10.2196/resprot.5278
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Internet Addiction with Anxiety Disorders: Treatment Protocol and Preliminary Before-After Results Involving Pharmacotherapy and Modified Cognitive Behavioral Therapy

Abstract: BackgroundThe growth of the Internet has led to significant change and has become an integral part of modern life. It has made life easier and provided innumerous benefits; however, excessive use has brought about the potential for addiction, leading to severe impairments in social, academic, financial, psychological, and work domains. Individuals addicted to the Internet usually have comorbid psychiatric disorders. Panic disorder (PD) and generalized anxiety disorder (GAD) are prevalent mental disorders, invo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(31 citation statements)
references
References 74 publications
1
29
0
1
Order By: Relevance
“…Effect sizes were calculated for each outcome variable assessed in each study. Two studies (i.e., Santos et al, ; Young, ) reported effect sizes considered to be exceedingly high (Hedges' g > 3). These outcomes were considered outliers.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Effect sizes were calculated for each outcome variable assessed in each study. Two studies (i.e., Santos et al, ; Young, ) reported effect sizes considered to be exceedingly high (Hedges' g > 3). These outcomes were considered outliers.…”
Section: Resultsmentioning
confidence: 99%
“…These outcomes were considered outliers. For this reason, two out of three outcome variables in Santos et al () were excluded and Young's () study was excluded altogether. Therefore, 12 studies were included in the meta‐analysis, which included a total of 580 participants.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Vários estudos demonstraram também a correlação entre ansiedade e adição à Internet (Santos et al, 2016;Weinstein et al 2015). Explica Young (2011) (Khoshakhlagh & Faramarzi, 2012;Lee & Leeson, 2015).…”
Section: Instrumentosunclassified